The dynamic effects of information on political corruption: Theory and evidence from Puerto Rico - Gustavo J. Bobonis; Luis R. Cámara Fuertes; Rainer Schwabe (Banco de México, 2012)
Does the disclosure of information about corrupt activities induce a sustained reduction in corruption? We use longitudinal data on audits of municipal governments in Puerto Rico to answer this question. We find that corruption is lower in municipalities audited before an election. However, these municipalities do not exhibit decreased levels of corruption in subsequent audits. Mayors in municipalities audited preceding the previous election have higher re-election rates, suggesting that audits enable voters to select more competent politicians. We present a political agency model that rationalizes the observed short-term and dynamic effects of information on corruption and re-election rates. We conclude that audit programs must be timely, sustained, and long-term commitments in order to be effective.
Keywords: D72; H41; K42; O17; 330; corruption; information; political agency